Two Empirical Approaches to the Study of Reasoning - Maurice A. Finocchiaro (Informal Logic, 1994)
David N. Perkins has studied everyday reasoning by an experimental-critical approach involving taped interviews during which subjects reflect on controversial issues and articulate their reasoning on both sides. The present author has studied scientific reasoning in natural language by an historical-textual approach involving the reconstruction and evaluation of the arguments in Galileo's Two Chief World Systems. They have, independently, reached the strikingly similar substantive conclusion that the most common flaw of informal reasoning is the failure to consider lines of argument supporting conclusions contrary to the one in fact reached. This article describes, compares, and contrasts their respective approaches, results, and theoretical frameworks.